MEME DI ERA DIGITAL DAN BUDAYA SIBER - murfianti, Fitri (Institut Seni Indoensia Surakarta, 2019)
Abstract The rapid dissemination of meme cannot be separated from the development of communication technology. Memes that circulate are not just a joke but a reflection of offline reality and presented with interesting visuals. Image processing technology encourages people to be more creative. This study focuses on the process of consumption, production, and distribution of internet memes and the formation of cyberculture because of these process by using the literature study method. In consuming this internet meme commodity, a